Perceptions and Achievement in Electrochemistry Using Flipped Classroom Model - Necor, Dexter (JPAIR Multidisciplinary Research, 2019)
The potential of flipped classroom instruction was undertaken to enhance the performance of students in learning electrochemistry. This study was to investigate the effects of the Flipped Classroom Model (FCM) on students’ performance in electrochemistry as well as their general perceptions. The study used a quasi-experimental method that utilized pre-test-post-test nonequivalent groups design. Students’ perception of FCM was based on a questionnaire. Results of the independent t-test noted that there was a significant difference between the two groups (t (26) =-2.281, p-value=0.031). The results suggested that the Flipped Classroom Group and Conventional Classroom Group are incomparable in terms of performance in electrochemistry after the intervention. The experimental group has a medium gain while the control group has a low gain as reflected by the normalized gain (Hake factor) values of 0.45 (SD = 8.32) and 0.22 (SD = 6.48), respectively. This only means that flipped classroom instruction has a generally positive effect on the achievement of students in learning electrochemistry. The students’ perceptions were positive. Students perceived that FCM helped them understand the concepts in electrochemistry easily. They also suggested that FCM was enjoyable, timely, and engaging. Lastly, the majority of the students agreed about the use of Flipped classroom instruction as an effective way to learn electrochemistry.